Trends in ensuring financial stability of the banking sector of Kazakhstan - Kerimkulova, D.D.; Zholamanova М.Т.; Larionova , I.V. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
In this scientific article, the authors consider the current state of the banking sector in Kazakhstan, as well as identify trends in ensuring its financial stability. The analysis of the dynamics of the structure of Kazakhstan’s second-tier banks over a ten-year period from 2010 to 2020 is carried out. The authors have compiled a chronology of consolidation and bankruptcy of the STB of Kazakhstan in the period from 1997 to the present. The analysis of the role of the banking sector in the economy of Kazakhstan allowed the authors to identify the reasons for the stagnation of the domestic financial market. The article also examines the impact of the coronavirus (Covid-19) on the banking system and, as a consequence, the trends of further development and transformation of banks. The researchers have identified factors influencing current and future trends in the development of the financial, including the banking sector. Within the framework of this study, the authors propose the main twelve trends in ensuring the financial stability of the banking sector in Kazakhstan.